(untitled) (International Journal of Natural Sciences, 2016)
This study was conducted to evaluate the socio-economic status of the duck farmers and to investigate the management practices of duck farming. Also attempt to identify the problems of duck farming in Biswanath and Balagonj upazila of Sylhet during a period from September to November 2014. For this study the information was collected by direct interview using a questionnaire from 60 duck farmers. Status of the duck farmers of the selected regions were investigated in the present study. The results reveal that most of the respondents duck farmers were < 35 years of age (52%) having with primary level of education (28%). In most of the farms there were local (deshi) ducks of 65.5% followed by KC (21.5%) and zinding (13%) respectively. For ducks feeding of the farmers depended on natural feed sources while some provided rice and broken rice (23.5%) rice polish and wheat bran (21.5%) and mixed feed (38%). Family size of the most of the farmers (57%) were large (size > 6 members). About 73% farmers had no training on duck farming and some of the farmers had training with short duration (7 to 15 days). Fifty percent of the farmers were made duck houses with tin-shed and wood having necessary floor space. Result of this study revealed that majority of the farmers (68%) had no idea about common duck diseases. The highest proportion of the farmers (65%) never followed the vaccination program regularly. There have some problems identified for duck farming including low price of duck meat and egg made ranked as most serious problems. Therefore, if the problems are addressed properly, the duck farming in haor areas in Sylhet, Bangladesh could be more profitable business for the farmers. International Journal of Natural Sciences (2015), 5(2) 73-79